Drug Abuse Prevalence and Effects in Coffee Shop Workers : A Cross Sectional Study - Makloph MG; Mohamed Masoud (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Drug abuse among population have become more common than before, coffee shops workersare of increasing chance to drug abuse, the facing of such big problem necessitates collection of informationregarding the prevalence of drug abuse types and effects on health , and this will result in prevention of itshazardous on population at all.Patients and Methods: cross- sectional study during the the first day of April 2019 till the last day ofSeptember 2019 , one hundred and twenty coffee shop workers were included. The workers were chosenfrom 12 randomly selected coffee shops located in rural and in urban areas. The data were gathered through aquestionnaire and urine samples from participants. The collected samples were taken to the lab and screenedfor drug abuse using dip stick, thin layer chromatography (TLC) and gas chromatography (GC-MS). Thecollected data were organized, tabulated, and statistically analyzed using statistical package for socialscience (SPSS Inc, version 22).Results: the study showed that The prevalence of tramadol and cannabis and other synthetic drugs amongcoffee shop workers in urban and rural area nowdays more than before and their detection easily done byusing GC-MS. hazardous on health among abusers more than non abusers.Conclusion: The prevalence of drug abuse among coffee shop workers of increasing popular especiallytramadol , cannabis and other synthetic drugs, between all age groups in urban and rural area ,these drugsof abuse can be detected using dip stick , TLC and the most specific method of detection using GC-MS toconfirm the results. Countries should plan for facing this cancer due to its bad hazardous and consequenceson health , family and society .